Automated detection and segmentation of intracranial hemorrhage suspect hyperdensities in non-contrast-enhanced CT scans of acute stroke patients - Schmitt, Niclas; Mokli, Yahia; Weyland, Charlotte S.; Gerry, S.; Herweh, Christian; Ringleb, Peter A.; Nagel, Simon (European radiology, 2022)
Artificial intelligence (AI)-based image analysis is increasingly applied in the acute stroke field. Its implementation for the detection and quantification of hemorrhage suspect hyperdensities in non-contrast-enhanced head CT (NCCT) scans may facilitate clinical decision-making and accelerate stroke management.